Prospects of Sharia Governance in Islamic Finance Industry: Jurisdictions, Standards, and Implications - Wani, Athar Shahbaz; Dar, Showkat Hussain (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2022)
The paper aims to explore the establishment, organizational setup, and relevance of the international regulatory/standard setting institutions as Sharī‘ah governance platforms primarily AAOIFI (Accounting and Auditing Organization for Islamic Finance Institutions) and IFSB (Islamic Financial Services Board). The role of IIFA (International Islamic Fiqh Academy Jeddah) IFC (Islamic Fiqh Council of Muslim World League MWL) and ISRA (International Sharī‘ah Research Academy for Islamic Finance) and supportive Shari ‘ah compliance platforms for Islamic Finance Industry (IFI) in the corporate and academic dimensions. The study is qualitative analysis of related Guiding Principles, which enshrine the Sharī‘ah governance framework (SGF) in IFI. The discussion highlights that the (SGF) is the particular aspect in the Islamic Finance Industry (IFI), which embodies the legitimacy of instruments, and generates the trust of stakeholders and shareholders in Islamic finance. The paper shows that analysis will support the understanding of Sharī‘ah governance and jurisdiction of the Islamic finance industry in the contemporary Banking and finance sector. The outcome of the predicted hypothesis will enable to suggest and modify the ongoing banking practices in Islamic corporate with strict adherence to the sharīa standards.